On the road again: The barriers and benefits of automobility for people with disability. (January 2018) - Darcy, Simon; Burke, Paul Francis
Highlights: Examines transport disadvantage to modified private vehicles for people with disability. Explores automobility as an essential area of policy development for the active citizenship. Presents the first quantitative evidence of the barriers and benefits of auto mobility. Analyses the complexity of understanding the heterogeneity of disability and support needs. Identifies the key components of barriers and benefits of automobility. Abstract: The UN Convention on the Rights of Persons with Disability (PWD) has been signed by over 160 nations to achieve greater social participation, with public and private transport clearly identified as an area to improve accessibility. Whilst the majority of scholarly work has focused on public transport needs, less research has examined the barriers or benefits of access to private modified vehicles for PWD. In this exploratory study, a Delphi technique with health experts, researchers, drivers and funding agencies developed an instrument to examine the barriers and benefits of access to private modified vehicles for PWD. An online survey was completed by 287 drivers and carers to report on barriers to private modified vehicles, whilst a sub-set of 190 drivers with access to a private modified vehicle reported on experientially derived benefits. A factor analytic approach identified how financial and informational barriers vary with respect to several characteristics including disability type and level of support needs. Factors relating to independence, social and recreational benefits are perceived as more valued experientially derived benefits relative to benefits relating to employability and ability to enjoy downtime. Benefits in the form of independence are greater among drivers and owners, those with an acquired condition, less complex mobility and everyday support needs, whilst little difference emerged in terms of the social and downtime benefits. The findings inform policy development and funding opportunities to provide insight and evidence into the barriers, but also benefits and variation in private transport needs among PWD.